Studies in Personnel and Industrial Psychology - Boivin, Jean (Relations industrielles / Industrial Relations, 1967)
This article reviews "Studies in Personnel and Industrial Psychology" the Revised Edition, by Edwin A. Fleishman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z